Evaluation of Multi-GNSS High-rate Relative Positioning for Monitoring Dynamic Structural Movements in the Urban Environment - Kaloop, Mosbeh; Yigit, Cemal; El-Mowafy, Ahmed; Bezcioglu, M.; Hu, J.; Dindar, A (Taylor and Francis, 2020)
Skyscrapers cause both limited sky-view and multipath error when using Global Navigation Satellite System (GNSS) measurements for monitoring structural movements. To reduce multipath errors, cut-off elevation angle can be set to a high value such as 30°−40°. However, in the case of employing high cut-off elevation angles, the use of GPS only may not provide adequate positioning solutions. To overcome this problem, Galileo and GLONASS observations are combined with GPS observations. This study experimentally investigates the contribution of multi-GNSS for studying the effects of different cut-off elevation angles on the accuracy of high-rate GNSS results for detecting characteristics of dynamic motions for structural health monitoring (SHM). The filtration design, noise level and Signal-to-Noise Ratio (SNR) of high-rate GNSS measurements of GPS-only, GPS/Galileo, GPS/GLONASS and GPS/GLONASS/Galileo are assessed for different cut-off elevation angles. The results demonstrate that the SNR of GNSS solutions for GPS/GLONASS and GPS/GLONASS/Galileo is the highest, which signifies their use in SHM. The accuracy of the dynamic movements of structures can be attained to 2 mm, on average, using multi-GNSS measurements even when using high cut-off elevation angles up to 40°. The precision of GPS/GLONASS and GPS/GLONASS/Galileo systems with different cut-off elevation angles was high when referenced to LVDT.